Effect of adding fermented split yellow pea flour as a partial replacement of wheat flour in bread. Issue 1 (18th June 2019) - Bourré, Lindsay; McMillin, Kasia; Borsuk, Yulia; Boyd, Lindsey; Lagassé, Shelley; Sopiwnyk, Elaine; Jones, Stuart; Dyck, Adam; Malcolmson, Linda
Abstract: The effect of adding fermented split yellow pea flour (SYPF) as a partial replacement for wheat flour in bread was examined. Three sourdough culture levels (3%, 6.5%, and 10%) and two fermentation times (1 and 4 hr) were evaluated. Total titratable acidity of ferment was measured to determine acid development. Bread was baked using three ferment inclusion levels (25%, 35%, and 45%) for each of the six treatment combinations. Nonfermented control bread was baked for each inclusion and culture level by adding the equivalent amount of SYPF and culture to the formulation. Bread was scored for quality and assessed for specific volume, crumb colour, C‐Cell properties, and flavour. Significant main effects were found for inclusion level, culture level, and fermentation time, and a significant Inclusion level × Fermentation time interaction was found for crumb firmness and cell diameter. Breads made with nonfermented SYPF and 10% culture had good flavour with only minor reductions in bread quality compared with a 100% wheat control bread. For the breads made with fermented SYPF, the ferment made with 10% culture fermented for 1 hr and added at an inclusion level of 25% had the most acceptable flavour and bread quality characteristics.